Regulating effects of anthraquinone substituents and additives in photo-catalytic oxygenation of p-xylene by molecular oxygen under visible light irradiation. (August 2021) - Jiang, Dabo; Zhang, Qiao; Yang, Long; Deng, Youer; Yang, Bo; Liu, Yachun; Zhang, Chao; Fu, Zaihui
Abstract: This paper reports that the optical properties of anthraquinone (AQ) and its photo-catalytic performance in the visible light-driven p -xylene (PX) oxidation can be fine-tuned and improved through varying its skeleton substituents at the molecular level, and the electron-withdrawing substituent exhibits a better improvement effect than the electron-donating one. The best catalyst 2-carboxyanthraquinone (AQ-COOH) can achieve 70.9% PX conversion and 88.2% p -toluic acid selectivity under visible light illumination and 1 atm O2 pressure. The addition of benzenesulfonic acid in the above photocatalytic system can further increase PX conversion to 86.7%, along with a significant improvement in the selectivity of p -carboxybenzaldehyde and terephthalic acid, which likely originates from the unique recombination behavior of the photo-generated charge carriers of the catalyst and the additive driven by the strong interactions between their aromatic skeletons and acidic substituents. Furthermore, AQ-COOH can achieve almost quantitative yield of acetylacetone in ethylbenzene photooxidation and the regulating effect of toluene's para-position substituents on its reactivity is also reported in the AQ-COOH photocatalysis system. Based on quenching tests and EPR spectral characterizations, the oxygen vacancies (h + ), superoxide free radicals (O2 - ) and singlet oxygen ( 1 O2 ) as the photo-generated active species are involved in the proposed photo-catalysis mechanism. Graphical abstract: Image 1 Highlights: AQs-based photo-catalytic protocol is very efficient for PX oxidation to p -TA. This protocol uses inexpensive visible light and O2 /air as green reactants. This protocol employs mild reaction conditions and its operating is very simple. This protocol has a good adaptability for the photooxidation of other substituted toluene. Photosensitive PhSO3 H plays a unique adjusting effect in this photo-catalytic protocol.